LEARNING OF SCIENCE WITH INQUIRY LEARNING MODELS WITH PICTORIAL RIDDLE THE RELATIONSHIP WITH THE CRITICAL THINKING SKILLS OF SMP STUDENTS - Reni Aprilia; I Ketut Mahardika; Iwan Wicaksono (Program Studi Pendidikan IPA FKIP Universitas Jember, 2020)
The inquiry learning model is a learning model that encourages student activity in learning activities. This inquiry learning model is accompanied by one of the learning media namely pictorial riddle in the form of puzzle images. This study aims to examine the effect of science learning with inquiry learning models accompanied by pictorial riddle relation to critical thinking skills of junior high school students. This type of research is an experiment using a pre-test post-test control group design. The study population was Grade VII students of SMP Negeri 1 Ambulu, sampling using a homogeneity test. The data analysis technique uses Independent samples t-test. The results of the Kolmogorov Smirnov normality test showed that both samples were normally distributed, so the hypothesis test uses a parametric statistical test called the Independent Sample T-test. Based on the results of the Independent Sample T-test, there is a significant influence on the results of critical thinking skills.